The Rise of the “We” Narrator in Modern American Fiction - Ruth Maxey (European Journal of American Studies)
Historically, the first-person plural narrator has been rare in US fiction, and it is both enigmatic and technically demanding. Yet an increasing number of American novelists and short story writers have turned to this formal device over the past 20 years and particularly since 9/11. How might one account for this rise in “we” narration, a trend that surprisingly few commentators have identified, questioned or examined at any length? What are the implications of telling a story in this difficult, even risky way? And in light of the formal challenges it poses to reader as well as writer, why have contemporary works of fiction that are told collectively often been critically and commercially successful? In this essay, I will attempt to answer such questions, examining how US writers from William Faulkner to Jeffrey Eugenides, and Kate Walbert to Julie Otsuka have used the collective narrator in short stories and longer fiction and finally reflecting upon the use of “we” in recent American political discourse.